How many different types of femora are there in primary hip osteoarthritis? An active shape modeling study. Issue 3 (19th November 2013) - Merle, C.; Waldstein, W.; Gregory, J.S.; Goodyear, S.R.; Aspden, R.M.; Aldinger, P.R.; Murray, D.W.; Gill, H.S.
ABSTRACT We assessed the variation in proximal femoral canal shape and its association with geometric and demographic parameters in primary hip OA. In a retrospective cohort study, the joint geometry of the proximal femur was evaluated on radiographs and corresponding CT scans of 345 consecutive patients with end‐stage hip OA. Active shape modeling (ASM) was performed to assess the variation in endosteal shape of the proximal femur. To identify natural groupings of patients, hierarchical cluster analysis of the shape modes was used. ASM identified 10 independent shape modes accounting for >96% of the variation in proximal femoral canal shape within the dataset. Cluster analysis revealed 10 specific shape clusters. Significant differences in geometric and demographic parameters between the clusters were observed. ASM and subsequent cluster analysis have the potential to identify specific morphological patterns of the proximal femur despite the variability in proximal femoral anatomy. The study identified patterns of proximal femoral canal shape in hip OA that allow a comprehensive classification of variation in shape and its association with joint geometry. Our data may improve future stem designs that will optimize stem fit and simultaneously allow individual restoration of hip biomechanics. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:413–422, 2014.